Precise determination of phonon constants in lead-free monoclinic (K0.5Na0.5)NbO3 single crystals - Rafiq, Muhammad Asif (2017)
A polarized Raman analysis of ferroelectric (K0.5Na0.5)NbO3 (KNN) single crystals is presented. The Raman modes of KNN single crystals are assigned to the monoclinic symmetry. Angular-dependent intensities of A', A\", and mixed A' + A\" phonons have been theoretically calculated and compared with the experimental data, allowing the precise determination of the Raman tensor coefficients for (non-leaking) modes in single-domain monoclinic KNN. This study is the basis for non-destructive assessments of domain distribution by Raman spectroscopy in KNN-based lead-free ferroelectrics. (C) 2014 Author(s). All article content, except where otherwise noted, is licensed under a Creative Commons Attribution 3.0 Unported License.